Construction of fluorescence system of felodipine–tetracyanovinyl–2,2′-bipyridine complex - Lang Yan; Zeng Yuanjun; Zhang Chunbin; Lv Kuilin (Green Processing and Synthesis, 2023)
Felodipine (FEL)–tetracyanoethylene (TCNE)–2,2′-bipyridine (Bpy) complex was prepared with FEL, TCNE–Bpy and characterized by fluorescence, ultraviolet, and infrared. By exploring the concentration and dosage of Bpy, it was found that 1 mL 2 × 10−3 mol‧L−1 of Bpy had the best effect. The sequence of reagent addition was determined to be followed by FEL, then by TCNE, and then followed by Bpy. The concentration of FEL was 2.5 × 10−4 to 9.0 × 10−3 mol‧L−1, which had a good linear relationship with fluorescence intensity. The compound had good accuracy, precision, and specificity, and could be used for the determination of phelodipine content in FEL sustained-release tablets.